Cloning of the complete DNA genomes of four bean-infecting geminiviruses and determining their infectivity by electric discharge particle acceleration - Gilbertson, R.L.; Faria, J.C. de; Hanson, SF; Morales, Francisco José; Ahlquist, P.G.; Maxwell, D.P.; Russell, D.R. (Scientific Societies, 1991)
Geminiviruses are small plant viruses that encapsidate a single-stranded circular DNA and form double-stranded DNAs in infected plants. Infection of economically important hosts with cloned DNAs of geminiviruses frequently has been difficult. Four isolates of bipartite bean-infecting geminiviruses (bean golden mosaic geminivirus isolates from Brazil [BGMV-BZ], Guatemala [BGMV-GA], and the Dominican Republic [BGMV-DR]; and bean dwarf mosaic geminivirus from Colombia [BDMV-CO]) were cloned; full-length cloned double-stranded DNA components A and B of each isolate were not infectious when mechanically coinoculated onto bean primary leaves by surface abrasion but were infectious when coinoculated into radicles of beans (Phaseolus vulgaris) by electric discharge particle acceleration. This novel method for the introduction of cloned geminiviral DNA into plants was extremely efficient and resulted in symptom expression in as few as 7 days. Moreover, infection of beans by cloned DNAs of BGMV-BZ, which has never been mechanically transmitted as virions or cloned DNAs, indicated that this procedure circumvents plant barriers to mechanical transmission. Three engineered mutants of BGMV-GA component A were constructed and separately introduced into beans with wild-type BGMV-GA component B, and disease phenotypes determined. Soybeans (Glycine max) also were infected with cloned DNAs of BGMV-BZ, BGMV-GA, and BDMV-CO, demonstrating a potentially important alternate host for these viruses. Particle acceleration will facilitate genetic analysis of bean-infecting geminiviruses and may allow for the efficient introduction of viral nucleic acids or virions of other viruses into hosts that are refractory to mechanical transmission.